2022
DOI: 10.3390/v14050990
|View full text |Cite
|
Sign up to set email alerts
|

Gga-miR-30c-5p Enhances Apoptosis in Fowl Adenovirus Serotype 4-Infected Leghorn Male Hepatocellular Cells and Facilitates Viral Replication through Myeloid Cell Leukemia-1

Abstract: Fowl adenovirus serotype 4 (FAdV-4) is the primary causative agent responsible for the hepatitis-hydropericardium syndrome (HHS) in chickens, leading to considerable economic losses to stakeholders. Although the pathogenesis of FAdV-4 infection has gained attention, the underlying molecular mechanism is still unknown. Here, we showed that the ectopic expression of gga-miR-30c-5p in leghorn male hepatocellular (LMH) cells enhanced apoptosis in FAdV-4-infected LMH cells by directly targeting the myeloid cell leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…miR-30c is found to impair the IFN-I signaling by targeting the 3’ UTR of IFNAR2 and JAK1, ultimately promoting the replication of PRRSV ( Figure 2B , Table 1 ) ( 107 , 108 ). In addition to PRRSV, gga-miR-30c-5p also can facilitated the replication of fowl adenovirus serotype 4 by directly targeting myeloid cell leukemia-1 ( 109 ). Avian reovirus (ARV) significantly upregulates the gga-miR-30c-5p expression, and gga-miR-30c-5p can inhibit the ARV-induced autophagy by targeting autophagy related 5, thereby suppressing ARV proliferation ( 110 ).…”
Section: Roles Of Mirnas In Host Response To Prrsv Infectionmentioning
confidence: 99%
“…miR-30c is found to impair the IFN-I signaling by targeting the 3’ UTR of IFNAR2 and JAK1, ultimately promoting the replication of PRRSV ( Figure 2B , Table 1 ) ( 107 , 108 ). In addition to PRRSV, gga-miR-30c-5p also can facilitated the replication of fowl adenovirus serotype 4 by directly targeting myeloid cell leukemia-1 ( 109 ). Avian reovirus (ARV) significantly upregulates the gga-miR-30c-5p expression, and gga-miR-30c-5p can inhibit the ARV-induced autophagy by targeting autophagy related 5, thereby suppressing ARV proliferation ( 110 ).…”
Section: Roles Of Mirnas In Host Response To Prrsv Infectionmentioning
confidence: 99%
“…To dissect the roles of miRNAs in host, RNA sequencing was performed in LMH cells infected with FAdV-4 ( Haiyilati et al., 2022 ). During this study it was found that the expression of 552 miRNAs in were altered.…”
Section: The Potential Regulatory Effect Of Fadv-4 Infection On Ncrnasmentioning
confidence: 99%